2020
DOI: 10.3390/su13010162
|View full text |Cite
|
Sign up to set email alerts
|

Getting Young Drivers to Buckle Up: Exploring the Factors Influencing Seat Belt Use by Young Drivers in Malaysia

Abstract: Many car drivers in Malaysia, especially young drivers, ignore the importance of wearing seat belts. This questionnaire study employed an extended version of the theory of planned behaviour (TPB) by including habit as a new construct to explain the factors influencing the behavioural intention and expectation of young Malaysian drivers to use seat belts. A total of 398 young drivers from the state of Selangor in Malaysia participated in this study. Analyses used a covariance-based structural equation modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 79 publications
3
10
0
Order By: Relevance
“…In line with previous studies [4,[6][7][8]10,[13][14][15][16], Hypothesis 2 was supported by both Model 2 and Model 3, where the PBC was also a significant influence. Some young drivers were overconfident about their driving skills and believed that they could easily conduct continuous lane-changing and be able to deal with any emergency.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In line with previous studies [4,[6][7][8]10,[13][14][15][16], Hypothesis 2 was supported by both Model 2 and Model 3, where the PBC was also a significant influence. Some young drivers were overconfident about their driving skills and believed that they could easily conduct continuous lane-changing and be able to deal with any emergency.…”
Section: Discussionsupporting
confidence: 90%
“…However, our study found that subjective norms significantly affected young drivers' willingness to engage in continuous lane-changing. Other studies on young drivers reported similar results [4][5][6][7][8]10,[12][13][14][15][16], which also confirmed that young drivers are more susceptible to the influence of family and friends.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations